Peran Guru dalam Meningkatkan Kecerdasan Spiritual Siswa di SMP Islam Ma’arif 02 Kota Malang - Nurul Hamidah Apriyanti; Muhammad Hanief; Ahmad Subekti (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Spiritual Intelligence is intelligence that elevates the function of the soul in order to have the ability to have a complete understanding of the teachings of Islam and be able to apply it properly in daily life. Being a man of faith and fear of Allah SWT and being able to actualize himself in accordance with the teachings and norms of Islam with an Islamic personality and moral character. This study uses a qualitative approach using interview techniques on the research subjects. The results showed that the development of spiritual intelligence was carried out through religious activities such as praying before starting learning, reading Asmaul Husna, Dhuha prayer, dhuhur prayer in congregation and reading and writing the Qur'an after school.